Political reforms asserting civic sovereignty - Kashyap Subhash C; Panandiker V A Pai (Delhi Konark, 2001)
This volume is carried out in two phases. It covers matters such as structural reforms of the electoral system, citizen-state relationship, multilevel governance, criminalisation, communalization, casteism, corruption, population control, poor administat
Keywords: India; Political reforms